‘Boks and bullets, coffins and crutches’ : an exploration of the body, mind and places of ‘Springbok’ South African soldiers in the First World War - Delport, Anri (Stellenbosch : Stellenbosch University, 2015)
Thesis (MA)--Stellenbosch University, 2015.